Mobile networks and management : 6th International Conference, MONAMI 2014, Würzburg, Germany, September 22-26, 2014, Revised selected papers /: 6th International Conference, MONAMI 2014, Würzburg, Germany, September 22-26, 2014, Revised selected papers. (2015) - Unknown
No abstract available